The theme of civil war in Russia in modern Russian literature: prospects of movement or completion of the cultural cycle? (A. Makushinsky and L. Yuzefovich) - Matveeva, Iuliia (Przegląd Wschodnioeuropejski, 2018)
In the article an attempt is made to apply the idea of nomadism to the process of transforming literary themes and plots that have taken shape and are fixed in the framework of certain national and cultural paradigms. In this case, it is a process of transforming such a topic, suchs so significant for Russian literature of the 20th century, as the Civil War in Russia. At present, it is experiencing a unique revival, but the means for its artistic implementation change significantly, as can be seen from the comparison of two contemporary novels dedicated to this topic: L. Yuzefovich’s “Winter Road” and A. Makushinsky’s “City in the Valley”. As a result of the analysis, it is concluded that in the sense of literary and artistic psychology, which assumes living in an image, the topic of the Civil War in Russia can be considered as closed, while the resources of historical evidence are able to open a new emotional, intellectual and artistic potential for it.